Aristotle's Nicomachean ethics : a critical guide - Miller, Jon, 1970- (New York : Cambridge University Press, 2013)
"Aristotle's Nicomachean Ethics is one of the most important ethical treatises ever written, and has had a profound influence on the subsequent development of ethics and moral psychology. This collection of newly-commissioned essays, written by both senior and younger scholars in the field, presents a thorough and close examination of the work. The essays address a broad range of issues including the compositional integrity of the Ethics, the nature of desire, the value of emotions, happiness, and the virtues. The result is a volume which will challenge and advance the scholarship on the Ethics, establishing new ways of viewing and appreciating the work for all scholars of Aristotle"--
Machine generated contents note: Introduction Jon Miller; Part I. Textual Issues: 1. On the unity of the Nicomachean Ethics Michael Pakaluk; Part II. Happiness: 2. Living for the sake of an ultimate end Susan Sauve;; 3. Contemplation and Eudaimonia in the Nicomachean Ethics Norman O. Dahl; 4. Aristotle on Eudaimonia, Nous, and divinity A. A. Long; Part III. Psychology: 5. Aristotle, agents, and action Iakovos Vasilou; 6. Wicked and inappropriate passion Stephen Leighton; 7. Perfecting pleasures: the metaphysics of pleasure in Nicomachean Ethics X Christopher Shields; 8. Aristotle's definition of non-rational pleasure and pain and desire Klaus Corcilius; 9. Non-rational desire and Aristotle's moral psychology Giles Pearson; Part IV. Virtues: 10. Beauty and morality in Aristotle T. H. Irwin; 11. Justice in the Nicomachean Ethics Book V Hallvard Fossheim.
Includes bibliographical references and index.
Keywords: Aristotle; Ethics